PEMANFAATAN KOLASE DENGAN MEDIA KERTAS DAN PLASTIK BEKAS DALAM KARYA MONOPRINT - Adi, Sigit Purnomo; Tri Marutama, I Gusti Ngurah (Institut Seni Indoensia Surakarta, 2019)
The use of used plastic and used paper to produce an alternative in the use of media in the process of visual processing specifically graphic artwork, this step is one of the efforts to save the environment with the help of art. By utilizing used goods, mostly used paper, plastic will not directly reduce the damage caused by plastic and paper materials. Paper and plastic are explored as sustainable media, while graphic art works are not only an aesthetic realm, but seniors as a way to provide awareness and care will discuss the environment. This creation uses monoprint and collage techniques as techniques for exploration and ideas in the art process.